Tourism suitability and community perception on development of the Cengklik Reservoir tourism, Boyolali Regency - Firdaus, Nur Salsabila; Purwanti, Frida; Ayuningrum, Diah; Sulardiono, Bambang (Universitas Malikussaleh, 2023)
Cengklik Reservoir is one of the water and waterfront tourism destinations in the Boyolali Regency which has an area of 327,44 ha. The condition of Cengklik Reservoir is currently undergoing revitalization and tourism development. The purpose of this study was to analyse the suitability of reservoir waters as a tourist attraction based on the Tourism Suitability Index, to determine the perceptions of tourists potential in the reservoir, and community perceptions of tourism development in the reservoir. The research was conducted in March - April 2023. The research methods used a case study with quantitative analysis to calculate the value of the Tourism Suitability Index and qualitative analysis to determine the perception of tourism potential from 30 tourist respondents and tourism development from 30 community respondents. Results of the TSI calculation of the Cengklik Reservoir for boat tours amounted to 2.40 (suitable) and fishing amounted to 3.00 (very suitable). The tourists perception of the Cengklik Reservoir as well as the communitys perception of tourism development were rated positively. These results indicate that the Cengklik Reservoir is suitable for tourism which is supported by the communitys perception of the tourist developmentKeywords: Cengklik Reservoir; Tourism Development; Tourism Potential; Tourism Suitability Index.